Baseline Risk Factors that Predict the Development of Open-angle Glaucoma in a Population: The Los Angeles Latino Eye Study - Jiang, Xuejuan (2012)
OBJECTIVE: To determine which baseline socio-demographic, lifestyle, anthropometric, clinical, and ocular risk factors predict the development of open-angle glaucoma (OAG) in an adult population. DESIGN: A population-based, prospective cohort study. PARTICIPANTS: A total of 3,772 self-identified Latinos aged 40 years and older from Los Angeles, California who were free of OAG at baseline. METHODS: Participants from the Los Angeles Latino Eye Study had standardized study visits at baseline and 4-year follow-up with structured interviews and a comprehensive ophthalmologic examination. OAG was defined as the presence of an open angle and a glaucomatous visual field abnormality and/or evidence of glaucomatous optic nerve damage in at least one eye. Multivariate logistic regression with stepwise selection was performed to determine which potential baseline risk factors independently predict the development of OAG. MAIN OUTCOME MEASURE: Odds ratios for various risk factors. RESULTS: Over the 4-year follow-up, 87 participants developed OAG. The baseline risk factors that predict the development of OAG include: older age (odds ratio [OR] per decade, 2.19; 95% confidence intervals [CI], 1.74-2.75; P<0.001), higher intraocular pressure (OR per mmHg, 1.18; 95% CI, 1.10-1.26; P<0.001), longer axial length (OR per mm, 1.48; 95% CI, 1.22-1.80; P<0.001), thinner central cornea (OR per 40 μm thinner, 1.30; 95% CI, 1.00-1.70; P=0.050) higher waist to hip ratio (OR per 0.05 higher, 1.21; 95% CI, 1.05-1.39; P=0.007) and lack of vision insurance (OR, 2.08; 95% CI, 1.26-3.41; P=0.004). CONCLUSIONS: Despite a mean baseline IOP of 14 mmHg in Latinos, higher intraocular pressure is an important risk factor for developing OAG. Biometric measures suggestive of less structural support such as longer axial length and thin CCT were identified as important risk factors. Lack of health insurance reduces access to eye care and increases the burden of OAG by reducing the likelihood of early detection and treatment of OAG.